2020
DOI: 10.3390/molecules25092112
|View full text |Cite
|
Sign up to set email alerts
|

Overlooked Scents: Chemical Profile of Soma, Volatile Emissions and Trails of the Green Tree Ant, Oecophylla smaragdina

Abstract: The green tree ant, Oecophylla smaragdina, is one of only two recognized species of weaver ants. While the identity and functions of chemicals produced and emitted by its congener O. longinoda have been studied quite extensively and serve as a valuable model in chemical ecology research, little comparable information is available about O. smaragdina. Although some analyses of chemicals produced and emitted by O. smaragdina have been reported, the literature is fragmentary and incomplete for this species. To ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 62 publications
(68 reference statements)
2
12
0
Order By: Relevance
“…This suggests that further studies to investigate the composition of O. longinoda gland secretions from different populations are necessary to enhance our understanding of gland chemistry. Nonetheless, our results agree with the composition of hydrocarbons recently reported for the poison gland secretions of the Asian weaver ant, O. smaragdina, which identified undecane, tricosane, and heneicosane as the most abundant components of the gland secretions [14], and formic acid previously identified as a major component of the poison gland secretions of carpenter ants (Camponotus spp.) [21]; the lemon ant, Myrmelachista schumanni [22]; and the red wood ant, Formica rufa [23].…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…This suggests that further studies to investigate the composition of O. longinoda gland secretions from different populations are necessary to enhance our understanding of gland chemistry. Nonetheless, our results agree with the composition of hydrocarbons recently reported for the poison gland secretions of the Asian weaver ant, O. smaragdina, which identified undecane, tricosane, and heneicosane as the most abundant components of the gland secretions [14], and formic acid previously identified as a major component of the poison gland secretions of carpenter ants (Camponotus spp.) [21]; the lemon ant, Myrmelachista schumanni [22]; and the red wood ant, Formica rufa [23].…”
Section: Resultssupporting
confidence: 93%
“…These additional components include a complex mixture of 32 hydrocarbons (51.6%), dominated by unsaturated alkanes, which ranged in chain length from 13 to 25 carbon atoms; saturated alkanes of chain length from 6 to 31 carbon atoms were also detected, as were 12 carboxylic acids (19.4%), dominated by short-chain fatty acids of chain length from two to seven carbon atoms; 5 aldehydes (8.1%); 3 alcohols (4.8%); 2 ketones (3.2%); 4 terpenes (6.5%); 3 sterols (4.8%) and 1 benzenoid (1.6%). Solvent-extracted glands and headspace volatiles gave similar profiles, dominated by hydrocarbons, which were also identified in the gland secretions of O. smaragdina [ 14 ]. However, we found that the headspace volatiles were richer in fatty acids than the solvent-extracted glands.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations